Effectiveness Of Balance Exercise On Improving Postural Balance: An Experimental Study - Baiq Nurainun Apriani Idris; Rahmat Pannyiwi; Yudi Muammar (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
ABSTRACT Postural balance is the body's ability to maintain a stable position while still or moving. Balance disorders increase the risk of falls, especially in adults and the elderly . Exercise is a non-pharmacological intervention aimed at improving postural control through proprioceptive training and muscle strengthening. This study aims to analyze the effectiveness of balance exercises. The effect of exercise on improving postural balance . The study used a quasi-experimental design with a pretest - posttest approach. with control group . The sample consisted of 40 respondents divided into intervention (n=20) and control (n=20) groups. The exercises were carried out for 4 weeks (3 times/week). Balance was measured using the Berg Balance Scale (BBS). The results showed a significant increase in BBS scores in the intervention group compared to the control (p < 0.001). It was concluded that balance Effective exercise significantly improves postural balance. Keywords: Balance Exercise , Postural Balance , Fall Risk, Proprioceptive Training